Effects of interlayer on the friction stir spot welding of stainless steel. (2022) - Raza, Muhammad Farhan; Yapici, Guney Guven
Abstract: Comparison of Interlayer Friction Stir Spot Welding (IL-FSSW) and conventional Friction Stir Spot Welding (FSSW) of 304 stainless steel is presented in this study. IL-FSSW is introduced as a novel spot-welding technique to avoid the keyhole formation at the weld spot. This process is employed to fabricate a joint between two stainless steel sheets. The utilization of an interlayer material prevents the occurrence of keyhole without any additional post-process treatment. In addition, the interlayer material also enhances ductility and provides a joint with a maximum lap shear load of 7 kN. The micrographs of the weld zone cross-section were recorded and it was observed that the interlayer material played a significant role in the development of the nugget zone by supporting the formation of a hook structure.